Falopletysmografické nálezy u pachatelů homosexuálnĕ pedofilních deliktů - Tichý, P (Casopis lekaru ceskych, 1991)
Using phalloplethysmographic tests comprising 20 coloured slides of four categories the authors examined 50 homosexual pedophil delinquents and a matched group of heterosexual men. The findings of the two compared groups differed significantly on exposure to three categories of erotic stimuli--adult heterosexual and homosexual objects and child homosexual objects. Only on projection of child heterosexual objects there were no statistically significant differences in the number and magnitude of positive vasomotor reactions recorded in the two groups. Men in the control group responded more frequently and more positively to adult heterosexual objects than homosexual pedophil delinquents. The latter responded more frequently positively to adult and child homosexual objects. In more than one quarter of the delinquents (13 men) a preference of child objects was found, i.e. a deviant pedophil orientation. In seven men the preference of child objects was without sexual differentiation, six men preferred homosexual child objects.
Keywords: homosexualita; mladiství; Homosexuality; Middle Aged; mužské pohlaví; Adult; Pedophilia; Child Abuse, Sexual; penis; pedofilie; pletysmografie; Humans; Penis; lidé středního věku; Plethysmography; sexuální zneužívání dítěte; dospělí; Adolescent; lidé; Male